Payroll taxes and firm performance - Johan Egebark; Niklas Kaunitz (Research Institute of Industrial Economics (IFN), 2017)
The Swedish employer paid payroll tax was reduced substantially for young workers in 2007, causing firms' average social fees to depend on the age structure of their employees. Using pre-reform conditions to define treated and control firms, we show that the lower costs induced by the reduced taxes have no impact on exit rates or profitability. We find negligible effects on gross investments, and negative, but not statistically significant, effects on labor productivity.
Keywords: D22; H22; J38; L25; 330; Payroll taxes; Labor costs; Profitability; Labor productivity; Investments; Windfall gain; Tax subsidy; Firm survival